2022
DOI: 10.1002/solr.202200550
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Surface Passivation for Highly Efficient Silicon Solar Cells Enabled by Innovative AlyTiOx/TiOx Electron‐Selective Contact Stack

Abstract: Passivating contacts based on transition metal oxides (TMOs) have the potential to overcome existing performance limitations in high‐efficiency crystalline silicon (c‐Si) solar cells, which is a significant driver for continuing cost/Watt reductions of photovoltaic electricity. Herein, innovative stacks of Al‐alloyed TiO x (Al y TiO x ) and pure TiO x as transparent electron‐selective passivating contacts for n‐type c‐Si surfaces are explored. An optimized stack of 2 nm Al y TiO x and 2 nm TiO x is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Therefore, the integration of such films into c-Si solar cells has been intensively investigated, as summarized in Figure , in order to demonstrate their performance at the device level and to benefit from their high transparency compared to Si-based contacts (a-Si:H and poly-Si) that cause parasitic absorption losses. Indeed, TiO x -based contacts have proven their ability to be integrated into a wide range of high-efficiency c-Si solar cell architectures, including either as full-area or partial-area rear contacts for front homojunction cells, , electron- or hole-selective passivating contacts in silicon heterojunction (SHJ) cells, , electron-selective passivating contacts in interdigitated back contact (IBC) cells, as well as antireflection coatings (ARC) for front homojunction cells . Unfortunately, the efficiency of such cells remains significantly below that of c-Si solar cells using Si-based contacts (a-Si:H and poly-Si), which have enabled recent record efficiencies in architectures including front-junction (FJ) and back-junction (BJ) tunnel oxide passivated contact (TOPCon) cells, SHJ, SHJ IBC, , and IBC , that are close to the theoretical limit for single-junction c-Si solar cells, as shown in Figure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the integration of such films into c-Si solar cells has been intensively investigated, as summarized in Figure , in order to demonstrate their performance at the device level and to benefit from their high transparency compared to Si-based contacts (a-Si:H and poly-Si) that cause parasitic absorption losses. Indeed, TiO x -based contacts have proven their ability to be integrated into a wide range of high-efficiency c-Si solar cell architectures, including either as full-area or partial-area rear contacts for front homojunction cells, , electron- or hole-selective passivating contacts in silicon heterojunction (SHJ) cells, , electron-selective passivating contacts in interdigitated back contact (IBC) cells, as well as antireflection coatings (ARC) for front homojunction cells . Unfortunately, the efficiency of such cells remains significantly below that of c-Si solar cells using Si-based contacts (a-Si:H and poly-Si), which have enabled recent record efficiencies in architectures including front-junction (FJ) and back-junction (BJ) tunnel oxide passivated contact (TOPCon) cells, SHJ, SHJ IBC, , and IBC , that are close to the theoretical limit for single-junction c-Si solar cells, as shown in Figure …”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, we have recently observed that exceptional surface passivation can be accomplished by capping 2 nm of Al y TiO x with 2 nm of TiO x (using TiCl 4 and H 2 O) at 75 °C to form an Al y TiO x /TiO x stack, in contrast to a reduced passivation quality obtained for single layers of TiO x or Al y TiO x , or the mirrored stack (TiO x / Al y TiO x ) on planar Si surfaces. 8 We have recently further improved upon this stack by incorporating ZnO to form an Al y TiO x /ZnO/TiO x structure, with similarly exceptional surface passivation but improved contact characteristics. 20 These enhancements in surface passivation performance after capping Al 2 O 3, Al y TiO x , or Al y TiO x /ZnO with a TiO x layer (using TiCl 4 and H 2 O) were argued to be due to atomic Cl being liberated during the deposition process and diffusing across the stack, accumulating at the Si surface and passivating Si dangling bonds.…”
Section: Introductionmentioning
confidence: 99%
“…As an evolutionary innovation from TiO x , the addition of Al doping (TiO x :Al) has demonstrated enhanced surface passivation and thermal stability. [ 26,27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Such a level of passivation is in line with our as‐deposited TiO x :Al layer ( J 0 = 26.5 fA cm −2 shown in Figure S8, Supporting Information) and also reported in the literature for samples passivated by a single layer of TiO x (without metallization). [ 42 ] It is noted that the reported V oc of cells based on a rear full‐area TiO x contact is in the range of 630–665 mV [ 13,27,42 ] corresponding to a J 0 value >300 fA cm −2 in Figure 8b, which implies that the good surface passivation of as‐deposited TiO x deteriorates in the device after metallization. The simulation highlights that strategies of maintaining good surface passivation of passivating contact after metallization are critical to achieving high V oc and high efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation